2006
DOI: 10.1200/jco.2006.24.18_suppl.3027
|View full text |Cite
|
Sign up to set email alerts
|

A phase I dose escalation study of BIBW 2992, an irreversible dual EGFR/HER2 receptor tyrosine kinase inhibitor, in patients with advanced solid tumours

Abstract: 3027 Background: BIBW 2992 is a novel, potent, orally bioavailable irreversible inhibitor of EGFR and HER2 receptor tyrosine kinases with IC50 values of 0.5 and 14 nM, respectively. Methods: Patients (pts) with advanced solid malignancies were enrolled. BIBW 2992 was given orally as a continuous once daily dose from 10 mg, doubled in successive cohorts until drug-related toxicity > grade 2, when escalation of no more than 50% was allowed. All pts had pharmacokinetic sampling and pre- and post-treatment ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Afatinib showed a manageable side effect profile in this study. Similar to previous studies with afatinib, the most frequently reported AEs were diarrhea and rash [ 18 , 19 , 25 , 26 ]. These AEs were generally manageable with appropriate treatment pause, supportive care, and dose reductions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Afatinib showed a manageable side effect profile in this study. Similar to previous studies with afatinib, the most frequently reported AEs were diarrhea and rash [ 18 , 19 , 25 , 26 ]. These AEs were generally manageable with appropriate treatment pause, supportive care, and dose reductions.…”
Section: Discussionsupporting
confidence: 81%
“…Evidence of clinical activity of afatinib monotherapy has also been demonstrated in phase I dose-escalation studies in advanced solid tumors. Stable disease (SD) was achieved in five of 14 BC patients participating in phase I monotherapy trials for up to 12 weeks (three patients) and up to 24 weeks (two patients) [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…BIBW‐2992 and HKI‐272 are irreversible‐type inhibitors in phase II studies. Dose‐limiting toxicities for BIBW‐2992 were diarrhea and skin rash, ( 32 ) whereas the most frequent severe adverse events for HKI‐272 were diarrhea and asthenia, surprisingly lacking skin rash. ( 33 ) Canertinib is also an irreversible‐type inhibitor and effective in preclinical cancer models, ( 34 ) but phase II studies were eventually disappointing, and further development was precluded.…”
Section: Discussionmentioning
confidence: 99%
“…BIBW 2992, an anilinoquinazoline designed to irreversibly bind EGFR and HER-2, suppresses the kinase activity of EGFR and HER-2 in tumor cells, including those with erlotinib-resistant isoforms (e.g., T790M) [95]. In phase I studies, BIBW 2992 has a demonstrated safety profile similar to that of other EGFR TKIs; associated AEs include rash and diarrhea [102,103]. In a single-arm phase II study (LUX-Lung 2) with a primary endpoint of RR, BIBW 2992 was administered to patients with advanced lung adenocarcinoma harboring activating EGFR mutations who are chemotherapy-naive (including patients who had received neoadjuvant/adjuvant chemotherapy) or who had experienced failure with first-line chemotherapy.…”
Section: Irreversible Tkismentioning
confidence: 99%